2005
DOI: 10.1159/000087846
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Catechol O-Methyltransferase Val108/158Met Polymorphism and Alexithymia

Abstract: It has been suggested that the characteristics of alexithymia result from deficits in frontal lobe functioning, and the prefrontal cortex is particularly dependent on the catechol O-methyltransferase (COMT) pathway. We investigated the relationship between COMT Val108/158Met, serotonin transporter coding sequence (5-HT transporter gene-linked polymorphic region; 5-HTTLPR) polymorphisms, and alexithymia.The study sample comprised 109 students at the Korea University. All participants were tested using the 20-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 44 publications
(26 reference statements)
5
23
1
2
Order By: Relevance
“…A major difference between these two studies is that while our data included individuals stabilized on methadone, de Haan's sample was undergoing detoxification and the observed changes in alexithymia may reflect dynamic withdrawal symptoms. Other work has suggested that alexithymia is a stable personality trait (Tolmunen et al, 2011), and it has been shown that genetic factors may contribute to alexithymia (Cairncross et al, 2013;Ham et al, 2005). Taken together with the present work showing little change over the follow-up, it appears that alexithymia is relatively stable in this population, regardless of variation in frequency of drug use over time.…”
Section: Discussionsupporting
confidence: 74%
“…A major difference between these two studies is that while our data included individuals stabilized on methadone, de Haan's sample was undergoing detoxification and the observed changes in alexithymia may reflect dynamic withdrawal symptoms. Other work has suggested that alexithymia is a stable personality trait (Tolmunen et al, 2011), and it has been shown that genetic factors may contribute to alexithymia (Cairncross et al, 2013;Ham et al, 2005). Taken together with the present work showing little change over the follow-up, it appears that alexithymia is relatively stable in this population, regardless of variation in frequency of drug use over time.…”
Section: Discussionsupporting
confidence: 74%
“…Clarity of Emotion was retained as the single dependent variable of interest. Similar to other exploratory behavioral genetics studies [10,39] and given that a relationship between C270T and alexithymia has not previously been established in the literature, we chose not to apply a Bonferroni correction for multiple comparisons (p < 0.05/3 = 0.017) in these analyses; adjusting the alpha threshold for significance might inappropriately increase the possibility that a real effect is missed among these data [40]. In all three analyses, a main effect emerged of C270T polymorphism on Clarity of Emotion, but there was no interaction between C270T and any of the COMT, DAT1, or ANKK1 genotypes 1 .…”
Section: Gene-gene Interaction Effectssupporting
confidence: 55%
“…COMT genotyping identified 30 Val/Val, 52 Val/Met, and 27 Met/Met individuals. Consistent with other researchers [10] and in order to maximize cell sizes, we condensed participants into Val homozygous and Met carrier (i.e., Met/Met and Val/Met) groups. DAT1 gene assay revealed 62 participants with the 10/10, 55 with the 9/10, 6 with the 9/9, 4 with the 10/11, 1 with the 3/3, 1 with the 8/10, and 1 with the 9/11 genotype.…”
Section: Genotyping Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast associations with polymorphisms of the dopamine system have not been reliably identified in Autism Spectrum Disorders. In a recent study Ham et al (2005) reported an association between the catechol-O-methyltransferase Val 108/158Met polymorphism and Alexithymia. Interestingly, an association was reported with the Valine allele which is associated with lowered prefrontal dopamine tone and is also thought to confer a small amount of risk to schizophrenia (Egan et al, 2001).…”
Section: Aetiology Of Alexithymiamentioning
confidence: 97%